An energy efficient clustering protocol for routing in Wireless Sensor Network. (3rd January 2011) - Zytoune, Ouadoudi; El Aroussi, Mohamed; Aboutajdine, Driss
In Wireless Sensor Network (WSN), the power supply is generally a non-renewable battery, consequently, energy effectiveness is a crucial factor. To maximise the battery life and therefore the duration of network service, a robust wireless communication protocol providing a best energy efficiency is required. In this paper, we present an Enhanced Low Energy Clustering Protocol for Routing in WSN (ELECP). The ELECP is a decentralised clustering algorithm that can be used in the case where the area sensed data are not perfectly correlated. The technique, used to partition the network, allows the distribution of energy load among any sensor nodes; this extends network lifetime. Simulation results show that the network lifetime is increased largely comparable to existing schemes.